Effect of Red Guava (Psidium guajava L.) Juice Concentration on Product Quality and Antioxidant Activity of Red Guava Synbiotic Yoghurt - Afifah, Diah Siti; Agustini, Rudiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Red guava juice has very strong antioxidant activity and has the potential to be processed into synbiotic functional beverage products that have health benefits. This study examined the effect of red guava juice concentration on product quality and antioxidant activity of red guava synbiotic yoghurt. Product quality tested included microbiological quality (total LAB) and chemical quality (pH value and Total Tritable Acid (TTA )value). The concentrations of red guava juice used were 0%, 10%, 20%, 30%, and 40%. Fermentation was carried out for 6 hours at 37⁰C by Lactic Acid Bacteria (LAB) from powdered mixed culture. Then organoleptic testing using the hedonic test, total LAB testing using the Total Plate Count (TPC) method, pH value testing using a pH meter, TTA value testing using the acid-base titration method, and antioxidant activity testing using the DPPH (2,2-diphenyl-1-picrylhydrazil) method. Test data were analyzed using SPSS software to determine the effect of red guava juice concentration on test results. The concentration of red guava juice in red guava synbiotic yoghurt affects the pH value, TTA value, and IC50 value as the result of antioxidant activity testing. Red guava juice concentration did not affect total LAB testing. Organoleptic assessment of red guava symbiotic yoghurt is in the range of like to like very much. The best formulation was red guava synbiotic yoghurt with 30% red guava juice concentration, which had strong antioxidant activity with an IC50 value of 59.637 ppm, pH value of 3.94, TTA value of 1.98%, and total LAB as much as 1.81x10⁸ colonies/g, so it has met the quality requirements of yoghurt according to Indonesian National Standard SNI 2981: 2009.